2020
DOI: 10.3389/fchem.2020.575288
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni3Fe2@NC/CC Integrated Electrode and Its Application in Zinc-Air Battery

Abstract: Reasonable design and development of a low-cost and high-efficiency bifunctional electrocatalyst for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is essential for promoting the development of Zinc-air battery technology. Herein, we obtained an integrated catalytic electrode, NiFe nanoparticles supported on nitrogen-doped carbon (NC) directly grown on the carbon cloth (designated as Ni 3 Fe 2 @NC/CC), by pyrolysis of bimetallic NiFe metal-orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…For example, enamelin, a large glycoprotein (Mw = 186 kDa), constitutes <5% of the extracellular matrix but is required for enamel mineral formation, as shown unequivocally in gene-targeted mouse models and human mutations resulting in hypoplastic AI. [24][25][26][27][28] No true enamel or apatite mineral ribbons are formed in Enam −/− mice. 29 The abnormally thin and disorganized enamel in AI patients suggests that enamelin is required to drive crystal formation, achieve structural organization of the apatite prisms, and develop optimal enamel thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, enamelin, a large glycoprotein (Mw = 186 kDa), constitutes <5% of the extracellular matrix but is required for enamel mineral formation, as shown unequivocally in gene-targeted mouse models and human mutations resulting in hypoplastic AI. [24][25][26][27][28] No true enamel or apatite mineral ribbons are formed in Enam −/− mice. 29 The abnormally thin and disorganized enamel in AI patients suggests that enamelin is required to drive crystal formation, achieve structural organization of the apatite prisms, and develop optimal enamel thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] No true enamel or apatite mineral ribbons are formed in Enam −/− mice. 29 The abnormally thin and disorganized enamel in AI patients suggests that enamelin is required to drive crystal formation, achieve structural organization of the apatite prisms, and develop optimal enamel thickness. 26,27 Despite its critical function in normal enamel formation, the mechanistic role of enamelin in the development of the mineral is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemically active surface area (ECSA) of electrocatalyst is known to be linearly proportional to the electrochemical double‐layer capacitance (C dl ). The C dl value of 12.2 mF cm −2 for FeNi/N−C‐900 shown in Figure 4S is much larger than those of catalysts in literature [40,41] . The high C dl indicates the benefits of FeNi nanoparticles and N−C substrate in exposing more electrochemical active sites, which is greatly relevant with the large BET surface area, abundant porous nanostructures, and ultrathin graphene‐like morphology.…”
Section: Resultsmentioning
confidence: 84%
“…The discharge potential plateau of FeNi/N−C‐900 is 1.23 V, which is slightly lower than lower than that of Pt/C−RuO 2 in Figure 8e. However, the specific discharge capacity of FeNi/N−C‐900 as cathode catalyst is 816.1 mAh g −1 , which is significantly higher than 712.1 mAh g −1 of Pt/C−RuO 2 and higher than the same type of cathode catalyst shown in Table S2 [41,44,45] . Finally, the cycle stability of Zn‐air battery is characterized by the cycle numbers of galvanostatic charge‐discharge, as shown in Figure 8f.…”
Section: Resultsmentioning
confidence: 91%
“…[23][24][25][26][27][28] Further, recent reports have indicated that the decoration of electrocatalysts directly on carbon cloth (CC) is a feasible method for improving their long-term electrocatalytic activities. [29][30][31][32][33][34][35][36][37][38][39] Moreover, this decoration can prevent the aggregation and leaching of the powder electrocatalyst from its substrate in liquid electrolytes during reactions, thus enhancing the electronic coupling between the electrocatalyst and substrate. Although there are many methods for synthesizing CoMn 2 O 4 for ECS applications, [19,20,[40][41][42][43][44][45][46][47][48][49][50] a few studies have attempted to specifically obtain surfactant, binder-free flexible electrodes.…”
Section: Introductionmentioning
confidence: 99%